Bandwidth Depletion - Measures for Advancing Gender Equality (MAGNET) Initiative (International Food Policy Research Institute, 2024)
The Measures for Advancing Gender Equality (MAGNET) initiative aims to broaden and deepen the measurement of women’s agency, based on the development of new tools and rigorous testing and comparison of both new and existing methods for measuring agency, and promoting the adoption of these measures at scale. By increasing the availability of innovative meaningful measures of agency for a broad range of contexts, we hope our work will lead to an improved understanding of what women’s agency is, how it manifests and how it can best be measured across contexts given the research question at hand. Cognitive bandwidth depletion and scarcity mindset are well-studied in laboratory settings, and there is strong evidence base for how it impacts poor people. Scarcity mindset induced by financial constraints may result in reduced bandwidth to attend to other pressing tasks, leading to trade-off thinking or giving preference to decisions that may have positive benefits for meeting immediate needs, but may result in negative impacts on longer-term well-being. Understanding bandwidth depletion could shed light on mechanisms behind why or how households prioritize certain decisions. Currently, there is limited evidence in non-Western contexts and from studies outside of laboratory settings, as well as a lack of measures that work in these contexts. This tool, Bandwidth Depletion, consists of a self-reported bandwidth scale and Simon’s circle task. This measurement tool is well suited for targeted thematic or impact evaluation surveys. Other variables that you may want to collect alongside the bandwidth depletion measure include education level, time use, household income, and food security. This data study includes following files. 1. A survey document (including implementation guidelines) 2. A statistical annex containing more information about the validation of the tool, as well as statistical guidance for analysis